2011
DOI: 10.1029/2011gl047910
|View full text |Cite
|
Sign up to set email alerts
|

View-angle dependent AIRS cloud radiances: Implications for tropical anvil structures

Abstract: Tropical anvil clouds play important roles in redistributing energy, water in the troposphere. Interacting with dynamics at a wide range of spatial and temporal scales, they can become organized internally and form structured cells, transporting momentum vertically and laterally. To quantify small‐scale structures inside cirrus and anvils, we study view‐dependence of the cloud‐induced radiance from Atmospheric Infrared Sounder (AIRS) using channels near CO2 absorption line. The analysis of tropical eight‐year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…For example, Gong andWu (2011, 2013) acknowledged the impact on AIRS cloudiness in the zonal direction, where they concluded that up to 50 % of AIRS view-angle asymmetry could be attributed to the systematic westward-tilted cloud structures in the UT. Aura Microwave Limb Sounder (MLS) day (night) forward-looking view is analogous to CloudSat northward (southward) looking view with a shallower viewing angle (∼ 86 • ).…”
Section: Formation Mechanism and Importance Of Systematic Ut Cloud Tiltmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Gong andWu (2011, 2013) acknowledged the impact on AIRS cloudiness in the zonal direction, where they concluded that up to 50 % of AIRS view-angle asymmetry could be attributed to the systematic westward-tilted cloud structures in the UT. Aura Microwave Limb Sounder (MLS) day (night) forward-looking view is analogous to CloudSat northward (southward) looking view with a shallower viewing angle (∼ 86 • ).…”
Section: Formation Mechanism and Importance Of Systematic Ut Cloud Tiltmentioning
confidence: 99%
“…Systematic cloud tilt structures can have profound impacts on cloud remote sensing and radiation calculations. For example, they partially account for the anisotropy of the cloud radiative forcing (Fu et al, 2000;Gong and Wu, 2013) and modulate the hydrological cycle (Naud et al, 2010). Neglecting or misrepresenting the cloud tilt induces additional biases in satellite retrieval of cloud properties (e.g., Hong et al, 2005) and increases uncertainty of model CRE estimation (e.g., Li and Barker, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete details of the IASI/AIRS processing system can be found in the Algorithm Theoretical Basis Document (ATBD) available at http://www.star.nesdis.noaa.gov/smcd/spb/iosspdt/qadocs/IASI_Phase2/. Note that the NUCAPS system implemented at NESDIS/STAR is essentially the same processing system, but adapted to the JPSS CrIS/ATMS sensors currently being flown on Suomi NPP [Gambacorta et al, 2012].…”
Section: Ir Sounder Calc à Obs Analysesmentioning
confidence: 99%
“…The cloud-clearing methodologies for IASI and CrIMSS [e.g., the NOAA-Unique CrIS/ATMS Processing System, NUCAPS; Gambacorta et al, 2012], are essentially the same as that used for AIRS [Susskind et al, 2003], whereby a clear-column IR radiance spectrum is derived for a field-of-regard (FOR) consisting of a "golf-ball" of K = 2 Â 2 (for IASI), or K = 3 Â 3 (for CrIS/ATMS and AIRS), IR FOVs overlapping 1 microwave (MW) FOV, with a nadir spatial resolution of '50 km. The cloud-clearing method basically assumes that differences among the IR FOV are solely due to clouds, then proceeds to extrapolate a clear-column spectrum (the cloud-cleared radiance),R n , from a linear combination of collocated FOVs, that is [Susskind et al, 2003] …”
Section: Overview Of Ir Sounder Cloud-clearingmentioning
confidence: 99%